Field Evaluation of Biological Control Measures against Bacterial Soft Rot (Pectobacterium carotovorum) on Tomato in Taraba State, Nigeria - Umaru, Yakubu; Tunwari, Bilkoya Adamu; Luka, Benjamin (Kwaghe International Journal of Sciences and Technology, 2026)
Bacterial soft rot caused by Pectobacterium carotovorum is one of the most destructive diseases affecting tomato production worldwide, creating a need for sustainable and effective management strategies under field conditions. This study evaluated the effectiveness of selected biological control agents and botanical extracts in managing bacterial soft rot of tomato in Wukari, Taraba State, Nigeria. The experiment was conducted using a randomized complete block design with three replications. The treatments consisted of neem extract, garlic extract, Bacillus subtilis, Trichoderma harzianum, Mancozeb, and an untreated control. Data were collected on disease incidence, disease severity, plant growth parameters, including plant height and number of leaves, and yield parameters, including number of fruits per plant, fruit weight, and total yield. The data were analyzed using analysis of variance, and treatment means were separated using Duncan’s multiple range test at the 5% probability level. The results showed that all treatments significantly reduced disease incidence and severity compared with the untreated control. The lowest disease incidence and severity were recorded in plots treated with B. subtilis and T. harzianum, which also significantly improved plant growth and yield parameters. The highest fruit yield, 19.8 t ha⁻¹, was obtained from plots treated with B. subtilis, whereas the untreated control recorded the lowest yield, 12.4 t ha⁻¹. The study concludes that biological control agents, particularly B. subtilis and T. harzianum, are effective in suppressing bacterial soft rot and improving tomato productivity. These findings contribute to sustainable tomato disease management by highlighting the potential of biological control agents as environmentally compatible alternatives for reducing disease pressure and enhancing yield under field conditions.